2010
DOI: 10.5539/ijbm.v5n10p75
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between Quality of Work Life and Organizational Commitment amongst Employees in Malaysian Firms

Abstract: Determining the quality of work life (QWL) of employees is an important consideration for employers interested in improving employees' job satisfaction and commitment. The purpose of this paper was to investigate the relationship between quality of work life and organizational commitment among a sample of employees in Malaysia. Seven QWL variables were examined namely growth and development, participation, physical environment, supervision, pay and benefits and social relevance were examined to determine their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 19 publications
2
73
1
1
Order By: Relevance
“…Given the fact that the importance of QWL is very eminent, Daud, (2010) proposed that a high level of QWL is compulsory for organizations to maintain attraction and retention employees. Richard E. Walton (1975) one of the protagonist of the work on QWL in his study titled "Criteria for Quality of Work life" elucidates the term with mention to eight extensive conditions of employment that represent desirable quality of work life.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that the importance of QWL is very eminent, Daud, (2010) proposed that a high level of QWL is compulsory for organizations to maintain attraction and retention employees. Richard E. Walton (1975) one of the protagonist of the work on QWL in his study titled "Criteria for Quality of Work life" elucidates the term with mention to eight extensive conditions of employment that represent desirable quality of work life.…”
Section: Introductionmentioning
confidence: 99%
“…This relationship of high commitment and high involvement in job was found to be positively correlated with positive customer service attitude [63]. Daud [64] also reported that different dimensions of QWL to have distinguishing effects on organisational commitments and quitting intentions. Organisational commitment was found to have a positive and direct relationship in terms of QWL dimensions in sectors like banking, food and educationindustry [65]- [67].…”
Section: Hypotheses Testingmentioning
confidence: 92%
“…However, because QWL can be an outcome of organizational activities and at the same time a process of human resource management, researchers could not agree on one way to measure it (Cheung & Tang, 2009;Daud, 2010;Lau, 2000). The different organizational cultures and diverse social, economical, and political circumstances of different nations have helped researchers modify the meaning and measurement of QWL in ways that suit each country and maybe each organization.…”
Section: Conceptual Foundations Of Qwlmentioning
confidence: 96%
“…The importance of studying QWL stems from the belief that employees' work life impacts turnover, satisfaction, and organizational behavior in every aspect (Abdulla, 2009). Because of this, many researchers in the past one hundred years have sought to address different aspects of QWL (Asgari & Dadashi, 2011;Daud, 2010;Taylor, Cooper, & Mumford, 1979;Walton, 1975;Yaghi, Morris, & Gibson, 2007).…”
Section: Conceptual Foundations Of Qwlmentioning
confidence: 98%
See 1 more Smart Citation